The Soviet Union’s Invisible Weapons of Mass Destruction - Rimmington, Anthony. author. aut Link
XV, 269 p. 20 illus.
Keywords: This book focuses on Biopreparat, the Soviet agency created in 1974, which spearheaded the largest and most sophisticated biological warfare programme the world has ever seen. At its height, Biopreparat employed more than 30,000 personnel and incorporated an enormous network embracing military-focused research institutes, design centres, biowarfare pilot facilities and dual-use production plants. The secret network pursued major offensive R&D programmes, which sought to use genetic engineering techniques to create microbial strains resistant to antibiotics and with wholly new and unexpected pathogenic properties. During the mid-1980s, Biopreparat increased in size and political importance and also emerged as a major civil biopharmaceutical player in the USSR. In the wake of the collapse of the Soviet Union in 1991, an acute struggle for control of Biopreparat’s most valuable assets took place and the network was eventually broken-up and control of its facilities transferred to a myriad of state agencies and private companies. Anthony Rimmington is a former Senior Research Fellow at Birmingham University’s Centre for Russian, European and Eurasian Studies, UK. He has published widely on the civil life sciences sector in the post-Soviet states and on the USSR’s offensive biological warfare programme, including The Soviet Union’s Agricultural Biowarfare Programme: Ploughshares to Swords (Palgrave, 2021).